Antihistamines improve cardiovascular manifestations and other symptoms of long-COVID attributed to mast cell activation - Salvucci, Fabrizio; Codella, Roberto; Coppola, Adriana; Zacchei, Irene; Grassi, Gabriella; Anti, Maria Luisa; Nitisoara, Nicolita; Luzi, Livio; Gazzaruso, Carmine (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Long-COVID is a hardly defined condition and there are no effective therapies. Cardiovascular manifestations of Long-COVID include high heart rate, postural tachycardia, and palpitations. Previous studies have suggested that mast cell activation (MCA) may play a role in the pathophysiology of Long-COVID, including in the mechanisms of its cardiovascular manifestations. The aim of the study was to evaluate the effectiveness of a treatment with blockers of histamine receptors in Long-COVID patients who did not respond to other therapies.Methods: Fourteen patients (F/M=9/5; 49.5±11.5 years) and 13 controls (F/M=8/5; 47.3±8.0 years) with Long-COVID symptoms attributed to MCA were evaluated. Patients were treated with fexofenadine (180 mg/day) and famotidine (40 mg/day). Fatigue, brain fog, abdominal disorders, and increased heart rate were evaluated in treated and untreated patients at baseline and 20 days later.Results: Long-COVID symptoms disappeared completely in 29% of treated patients. There was significant improvement in each of the considered symptoms (improved or disappeared) in all treated patients, and the improvement grade was significantly greater in treated patients with respect to controls. No significant differences in the outcomes were observed in the controls.Our data confirm that histamine receptors blockade may be an effective target to successfully treat long-COVID. Our finding supports the underlying role of MCA in the pathophysiology of Long-COVID.